EVALUASI KINERJA KEUANGAN PEMERINTAH KABUPATEN MUSI BANYUASIN BERDASARKAN BESARAN SISA LEBIH PEMBIAYAAN ANGGARAN (SILPA) - Jumania Septariani; Deswati Supra (Institut Rahmaniyah Sekayu, 2023)
This study aims to determine the Performance Evaluation of the Musi Banyuasin Regency Government based on the Silpa Amount in the Regional Revenue and Expenditure Budget (APBD) in 2017-2020. Budget Calculation Excess Remaining was the remaining funds obtained from the actualization of regional income and installment payments for one period. Data collection techniques used were interviews and documentation. The data analysis technique used was descriptive qualitative research on the year 2017-2020 based on Silpa analysis, which was Rp.24.119.260.652 in 2017 and Rp.247.489.457.842 in 2018 and Rp.591.783.203.942 in 2019 and Rp.675.605.322.695 in 2020. The Financial Management of The Banyuasin Regency Government in 2017-2020 changed every year. This was indicated by the absorbed budget in which the revenue target was not achieved and not in accordance to the funds budgeted at the beginning of the period. This showed that the performance of the Musi Banyuasin Regency Government has not been good or less efficient in managing its financial planning.